2016
DOI: 10.3329/ajmbr.v1i3.26496
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and characterization of bacterial flora from the respiratory tract of apparently healthy sheep

Abstract: Abstract:Sheep is the common name for a group of grazing mammals that may be either wild or domesticated; the domesticated varieties are amongst the most widely distributed types of domestic animal, found in nearly all countries. Bangladesh is a densely populated developing country and its economy is primarily based on agriculture. The current study was designed for isolation, identification and characterization of bacterial flora from the upper respiratory tract of sheep. Thirty (30) apparently healthy sheep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…The results of Gram's staining of E. coli in this study are similar with the findings of Thomas et al (2005); similarly, the results for Staphylococcus spp. are same as reported by Brooks et al (2002) and Sarker (2009), the results for Salmonella spp. are same as of Cheesbrough (1985) and Sannat et al (2017), and results for Bacillus spp.…”
Section: Morphological Characterization Of the Isolated Bacteriasupporting
confidence: 91%
“…The results of Gram's staining of E. coli in this study are similar with the findings of Thomas et al (2005); similarly, the results for Staphylococcus spp. are same as reported by Brooks et al (2002) and Sarker (2009), the results for Salmonella spp. are same as of Cheesbrough (1985) and Sannat et al (2017), and results for Bacillus spp.…”
Section: Morphological Characterization Of the Isolated Bacteriasupporting
confidence: 91%
“…These clinical manifestations resembled to those described by [30]. The identi cation of M. haemolytica with biochemical methods is often challenging in some conditions due to antibiotic treatment, vaccination, transportation and storages [31]. Of the 213 cultures two (2) nasal swabs were tentatively identi ed as M.haemolytica.…”
Section: Discussionsupporting
confidence: 68%
“…[177][178][179] Bacteria of the respiratory tract of sheep have also been isolated and identified. 180 Among the virus diseases, the genetic characterization of PPR in goats, 181,182 isolation and characterization of contagious ecthyma (CE) in both the goats and sheep 183 and epidemiology and phylogenetic studies on CE in goats 184 have been reported from Bangladesh. [181][182][183][184] Molecular detection of cellular prion protein in goats have also been reported.…”
Section: Microbiological Researchmentioning
confidence: 99%